Rejecting Opposite Ideologies without Discriminating against Ideological Opponents? Understanding Nonbelievers' Outgroup Attitudes. Issue 1 (2nd January 2020) - Uzarevic, Filip; Saroglou, Vassilis; Pichon, Isabelle
Abstract: Several people fail to reject opposite ideologies without discriminating against opponents. Do nonbelievers make this distinction? Across two experiments in three cultures (total N  = 2064), we investigated participants' willingness to help a religious target involved in religious anti-liberalism (antiabortion), activism (promoting Christian ideas), or devotion (religious service); or a neutral cause (copying syllabus or visiting family). In comparison to a control condition (neutral target, neutral cause), nonbelievers–except French atheists, to some extent–made this distinction: they were unwilling to help the religious target when acting for any of the three religious causes, but not when acting for a neutral cause. Groups with opposite ideologies, here believers and nonbelievers, seem both similar and qualitatively dissimilar in their outgroup attitudes.